IDENTIFICATION OF RISK FACTORS AND SYMPTOMS OF CHRONIC KIDNEY DISEASE ON ELDERLY IN NURSING HOME ‘X’ PEKANBARU - Adhia, Dinda; Qalbi, Khairatul; Fannissa, Kintan A; Marindra, Fajri (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: At this time, Chronic Kidney Disease (CKD) is still a world health problem, CKD is usually undetected until it reaches the severe or terminal stage. CKD ranks 16th as a cause of death worldwide. Nationally, CKD has been the second largest expense following heart disease. This study was conducted to identify the symptoms and risk factors for chronic kidney disease in the elderly in social care institutions who are the population at risk. Methods: A descriptive study was conducted on 38 elderly people aged ≥60 years who are residents of nursing home 'X'. The residents of the nursing home who met the criteria of inclusion were interviewed and identified the risk factors and symptoms of CKD by conducting interviews using the available questionnaires and physical examination. Data were collected and presented in frequency distribution table. Results: from 38 respondents, 15 respondents had history of hypertension, 10 respondents had a history of diabetes mellitus, 16 respondents had history of smoking, 8 with history of NSAIDS use, and no one has history of kidney disease. The highest count of risk factor was found in 1 respondent (2.6%), meanwhile respondent with 1 and 2 risk factors was found in 11 respondents (28.9%). The most frequent symptom of CKD that appeared among respondents was decreased libido which 26 respondents experienced every day and the rarest symptom of kidney disease that appeared among respondents were restless legs which 35 respondents have never experienced. Conclusion: Almost every respondent had risk factor/s of CKD with the most frequent distribution of risk factor is 1-2 risk factor/s in one respondent and the most frequent symptom among respondents is impotence/decreased libido.